REINTERPRETASI NARASI DAN VISUAL WAYANG RAMAYANA DALAM DESAIN BUSANA KONTEMPORER SEBAGAI UPAYA PELESTARIAN BUDAYA: REINTERPRETATION OF RAMAYANA WAYANG NARRATIVE AND VISUAL ELEMENTS IN CONTEMPORARY FASHION DESIGN AS A CULTURAL PRESERVATION EFFORT - Vania Ardelia Putri; Achmad Haldani Destiarmand (Universitas Trisakti, 2025)
Reinterpretation of Ramayana Wayang Narative and Visual Elements in Contemporary Fashion Design as a Cultural Preservation Effort, Wayang kulit is a traditional Indonesian art form rich in aesthetic, spiritual, and moral values, yet its relevance is declining due to modernization. This study focuses on reinterpreting the Ramayana particularly the characters of Rama and Sita through contemporary fashion design to preserve cultural heritage. Utilizing a qualitative method, the research includes literature studies, field observations, and interviews with fashion and cultural experts. The outcome is a collection of wearable art pieces integrating wayang kulit visuals, Ramayana motifs, and modern fashion aesthetics. Targeted at younger generations, the designs aim to educate, promote cultural appreciation, and encourage dialogue between tradition and modernity within Indonesia’s creative fashion industry.